Developing Potential and Sharing Knowledge: How German Companies Can Gain a Foothold in Africa - Dirk Dohse; Sophia Fehrenbacher; Philipp von Carlowitz (Wirtschaftsdienst)
Abstract Africa is a continent of opportunities that is likely to play an increasingly important role in the future international division of labour. Yet, German companies’ economic activity and investment in Africa is still limited. This article examines how the digital transformation is changing the investment and innovation conditions in Africa, how German companies can utilise new opportunities resulting from these changes and how politics can foster greater commitment by German and European companies in Africa.